Spatial distribution, total length frequencies and otolith morphometry as tools to analyse the effects of a flash flood on populations of roach (Rutilus rutilus). Issue 1 (28th March 2017) - Morat, Fabien; Gibert, Pierre; Reynaud, Nathalie; Testi, Baptiste; Favriou, Pierre; Raymond, Virginie; Carrel, Georges; Maire, Anthony
Abstract: Floods are known to be the major source of natural variability and disturbance in stream ecosystems. However, the management and channelisation of large rivers have impacted the fluvial geomorphology and disconnected the main channel and floodplains used as nurseries by many species of fish. This study examines the influence of a first autumnal flood event of the Ardèche River on the roach population, Rutilus rutilus (Linnaeus, 1758), in the Caderousse reach on the Rhône River. This influence was evaluated through an analysis of the spatial distribution for the abundance and size of juvenile roach and an analysis of otolith shape. Juvenile roach from the three sections of the reach formed well‐defined local populations before and after the flood event. Juvenile roach were always more abundant in the less modified section (BPS) of the river than in the other sections (RES and TAIL). While the original primary river channel was directly impacted by the flash flood, no significant difference in otolith shape was observed before or after the flash flood. Our results suggest that this part of the reach provides refuge habitats used by fish during high flow events.